Física e matemática - uma abordagem construcionista: ensino e aprendizagem de cinemática e funções com auxilio do computador - Carvalho Júnior, José Carlos Nogueira de (2008)
This paper aims to investigate which contributions a constructionist approach on education would bring to the students learning process on the kinematics concepts, when compared to the traditional approach and which benefits the study of the syllabus of functions and kinematics, through the use of an auxiliary computational tool, can bring to their construction of knowledge. In order to achieve our objectives, we have developed a series of activities using the software Interactive Physics, examining the issues Launching of Bodies and Functions of 1st and 2nd degrees , using as theoretical framework the conceptions of Constructionism developed by Papert; the methodology based on elements of the Design Experiment, as for the role played by the teacher-researcher; the classification developed by Valente Description, Execution, Reflection and Purification to analyze the students procedures while using the software, as well as on Steve Monk s studies of the students understandings of the concept of functions based on a physical model. The research s subjects were second grade public high school students of São Paulo state; 16 students who had used the computational tool Constructionist Group and 32 students who had carried out only activities using paper and pencil the Traditional Group. After the accomplishment of the activities, the students were submitted a questionnaire and the groups performances were compared. The results showed that the students motivation, efforts and satisfaction while operating the software trying to solve their problems consisted in a pedagogical advantage of this type of approach. The understanding of the coefficient meanings and variables of the time functions of the movements studied through the diverse possibilities of analyses and control of these elements in the simulation environment provided by the software as well as the interpretation and graphical representation of these functions, have proved to be a more consistent learning, contributing to a more accurate understanding of the physical phenomena studied. Moreover, we have observed that a constructionist approach makes possible the study of the movement of the bodies more dynamically and not statically - feasible by the computational tool education - relating this study to the existing real phenomena in nature, which is the object of study of Physics